How important is the coast? A survey of coastal objectives in an Australian regional city. (September 2016) - Dutra, Leo X.C.; Dichmont, Catherine M.; van Putten, Ingrid E.; Thébaud, Olivier; Deng, Roy A.; Pascual, Ricardo; Owens, Randall; Jebreen, Eddie; Thompson, Carolyn; Warne, M.St.J; Quinn, R.; Bennett, J.; et al.
Abstract: Defining goals and objectives is a critical component of adaptive management of natural resources because they provide the basis on which management strategies can be designed and evaluated. The aims of this study are: (i) to apply and test a collaborative method to elicit goals and objectives for inshore fisheries and biodiversity in the coastal zone of a regional city in Australia; (ii) to understand the relative importance of management objectives for different community members and stakeholders; and (iii) to understand how diverse perceptions about the importance of management objectives can be used to support multiple-use management in Australia's iconic Great Barrier Reef. Management goals and objectives were elicited and weighted using the following steps: (i) literature review of management objectives, (ii) development of a hierarchy tree of objectives, and (iii) ranking of management objectives using survey methods. The overarching goals identified by the community group were to: (1) protect and restore inshore environmental assets; (2) improve governance systems; and (3) improve regional (socio-economic) well-being. Interestingly, these goals differ slightly from the usual triple-bottom line objectives (environmental, social and economic) often found in the literature. The objectives were ranked using the Analytical Hierarchical Process, where a total of 141 respondents from industry, government agencies, and community from across Queensland State undertook the survey. The environment goal received the highest scores, followed by governance and lastly well-being. The approach to elicit and rank goals and objectives developed in this study can be used to effectively support coastal resource management by providing opportunities for local communities to participate in the setting of regional objectives. Highlights: Mackay community acknowledges government and farmers' efforts to improve regional water quality. However, the community is increasingly concerned with coastal development issues. There is a need to improve governance systems to achieve sustainability outcomes in the region.